2015
DOI: 10.1021/cr500537t
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Characterization of Graphene–Nanoparticle Hybrid Materials for Bioapplications

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
395
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 647 publications
(419 citation statements)
references
References 345 publications
4
395
0
5
Order By: Relevance
“…field-effect transistor | Debye screening | surface modification | DNA aptamer receptor | polyethylene glycol N anoelectronic biosensors offer broad capabilities for label-free high-sensitivity real-time detection of biological species that are important to both fundamental research and biomedical applications (1)(2)(3)(4)(5)(6). In particular, field-effect transistor (FET) biosensors configured from semiconducting nanowires (1,2), single-walled carbon nanotubes (1,3,4), and graphene (1,5,6) have been extensively investigated since the first report of real-time protein detection using silicon nanowire devices (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…field-effect transistor | Debye screening | surface modification | DNA aptamer receptor | polyethylene glycol N anoelectronic biosensors offer broad capabilities for label-free high-sensitivity real-time detection of biological species that are important to both fundamental research and biomedical applications (1)(2)(3)(4)(5)(6). In particular, field-effect transistor (FET) biosensors configured from semiconducting nanowires (1,2), single-walled carbon nanotubes (1,3,4), and graphene (1,5,6) have been extensively investigated since the first report of real-time protein detection using silicon nanowire devices (7).…”
mentioning
confidence: 99%
“…In particular, field-effect transistor (FET) biosensors configured from semiconducting nanowires (1,2), single-walled carbon nanotubes (1,3,4), and graphene (1,5,6) have been extensively investigated since the first report of real-time protein detection using silicon nanowire devices (7). Subsequent studies have demonstrated highly sensitive and in some cases multiplexed detection of key analytes, including protein disease markers (8-10), nucleic acids (11)(12)(13), and viruses (14), as well as detection of protein-protein interactions (8,(15)(16)(17) and enzymatic activity (8).…”
mentioning
confidence: 99%
“…In the standard configuration of a FET, the electric current flows along a semiconductor channel connected to the source and drain electrodes. A third electrode, the gate contact, which is capacitively coupled to the device through a thin dielectric layer (typically SiO 2 ), modulates the conductance between these two electrodes [20,24].…”
Section: Fet-based Immunosensorsmentioning
confidence: 99%
“…Furthermore, HNCs can be controllably engineered with extremely rich structural and topological diversity, thus exhibiting integrated functionalities as well as novel properties stemming from the efficient electronic communication established between joint material domains. All these prerogatives are prohibited both to traditional colloidal nanocomposites that are constructed by exploiting weak (electrostatic or van der Waals) interactions or bifunctional molecules serving as linking bridges between the involved building blocks (Kamat, 2007;Quarta et al, 2007;Bigall et al, 2012;Tian et al, 2015;Yin et al, 2015) and to their heterocluster analogues (albeit frequently based on much larger nano-/micro-particle units) that are derived by assembly mechanisms relying on weak inter-particle forces, external perturbations, and the guide of templating substrates and interfaces Duguet et al, 2011;Gao and Fang, 2015;Vogel et al, 2015;Yan et al, 2015a,b;Yin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%